Structure Determination of [Au18(SR)14]1. Issue 10 (23rd January 2015) - Das, Anindita; Liu, Chong; Byun, Hee Young; Nobusada, Katsuyuki; Zhao, Shuo; Rosi, Nathaniel; Jin, Rongchao
Abstract Unravelling the atomic structures of small gold clusters is the key to understanding the origin of metallic bonds and the nucleation of clusters from organometallic precursors. Herein we report the X‐ray crystal structure of a charge‐neutral [Au18(SC6H11)14] cluster. This structure exhibits an unprecedented bi‐octahedral (or hexagonal close packing) Au9 kernel protected by staple‐like motifs including one tetramer, one dimer, and three monomers. Until the present, the [Au18(SC6H11)14] cluster is the smallest crystallographically characterized gold cluster protected by thiolates and provides important insight into the structural evolution with size. Theoretical calculations indicate charge transfer from surface to kernel for the HOMO–LUMO transition.